Perbaikan Varietas Mangga Agri Gardina 45 melalui Persilangan - Karsinah, Karsinah; Indriyani, Ni Luh Putu; Ali, Rusjamin Jadi (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
The Agri Gardina 45 as a new superior variety of mango has flavor such as Arumanis, yellowish-red peel color, early fruit and productive, but fruit size was relatively small, which is about 93-172 g/fruit with edible portion 64.62-64.65%. To increase the edible portion of Agri Gardina 45, this variety was crossed with mangoes which have edible portion > 70%. The aim of the reseach is to obtain progeny of crossing between Agri Gardina 45 with mangoes that have edible portions > 70%, and to observe the growth of the progenies from the crossing of both varieties. The research was conducted from January 2017 to December 2018 at Cukurgondang Experimental Field, Pasuruan, East Java. The crossing combinations were Agri Gardina 45 x Arumanis 143, Arumanis 143 x Agri Gardina 45, Agri Gardina 45 x Garifta Merah, Garifta Merah x Agri Gardina 45, and Agri Gardina 45 x Keitt. An evaluation of seedlings growth using the progenies obtained from the combination of these crossings. The results indicate that from 12,970 flowers that have been crossed, there were 30 F1 accessions of progenies were obtained. Growth evaluation of these progenies showed that the seedlings of 30 accessions of F1 have diverse growth. F1-12 (AG) showed the highest increase in height and stem diameter, while F1-31 (AG) have the smallest increase in height, stem diameter and leaves number. F1-23 (AG) shows the largest increase in leaves numberKeywords: Mangifera indica L., variety improvement, crossing